A Review of Current Bacterial Resistance to Antibiotics in Food Animals - Xu, Chunming; Kong, Lingqiang; Gao, Hanfang; Cheng, Xiyu; Wang, Xiumin (Frontiers in Microbiology, 2022)
The overuse of antibiotics in food animals has led to the development of bacterial resistance and wide spread of resistant bacteria in the world. Antibiotic resistant bacteria (ARB) and antibiotic resistant genes (ARGs) in food animals are currently considered as emerging contaminants, which are a serious threat to public health globally. The current situation of ARB and ARGs from food animal farms, manure and wastewater was firstly covered in this review. Potential risks on public health were also highlighted, as well as strategies (including novel technologies, alternatives, and administration) to fight against bacterial resistance. This review can provide an avenue for further research, development and application of novel antibacterial agents to reduce the adverse effects of antibiotic resistance in food animal farms.